Clinicopathologic Profile and Treatment Outcomes of Children With Diffuse Large B-cell Lymphomas: Experience From a Tertiary Cancer Center in India. Issue 3 (3rd April 2022) - Mande, Radnyi; Roy Moulik, Nirmalya; Shet, Tanuja; Narula, Gaurav; Prasad, Maya; Dhamne, Chetan; Bhat, Vasudeva; Cheriyalinkal Parambil, Badira; Shah, Sneha; Shridhar, Epari; Gujral, Sumeet; Banavali, Shripad
Abstract : Clinicopathologic profile and outcome of 15 children (15 years or above) with diffuse large B-cell lymphoma treated with MCP-842 protocol are reported. Eleven of 15 presented with advanced (stage-III/IV) disease. Post-2 cycles of chemotherapy, complete metabolic and morphologic response was documented in 10 (66%) and rest 5 (33%) with partial response achieved complete metabolic remission by end of treatment. At a median follow-up of 44 months (range: 16 to 79 mo), the 3-year event-free survival and overall-survival were 77.1%±11.7% and 85.7%±9.4%, respectively. Though majority of our patients had advanced disease, outcome on MCP-842 protocol was satisfactory.